USE OF MULTIMEDIA IN TEACHING OF «MEDICAL REHABILITATION» FOR INTERNS - Постовітенко, К.П. (World of Medicine and Biology, 2015)
The article highlights the features of the process of perception of modern human mind. The article discusses the possibility of using multimedia as one of the options for using these features to enhance the quality of education. The author describes the experience of using electronic (multimedia) presentations and videos in teaching of "Medical rehabilitation" for interns.
Keywords: perception; "clip-thinking"; teaching; multimedia; medical interns